Assessing the Effectiveness and Safety of Direct-acting Antiviral Treatment in Korean Patients with Hepatitis C Virus Genotype 1b or 2 at a Tertiary Care Hospital - Park, Mi Seon; Yang, Young-Mo; Park, Ki Hyun; Yoon, Hyonok; Kim, Ju Sin; Choi, Eun Joo (Korean Journal of Clinical Pharmacy, 2022)
Background: Direct-acting antivirals are recommended for the treatment of chronic hepatitis C virus in Korea. However, evaluationof direct-acting antiviral regimens in a real-world setting is limited. The aims of this study were to investigate the effectiveness andsafety of direct-acting antiviral treatment in Korean patients infected with chronic hepatitis C virus genotype 1b or 2 at a tertiary carehospital. Methods: This was a retrospective study conducted with patient data obtained between August 2015 and August 2019 atJeonbuk National University Hospital. The primary effectiveness endpoint was sustained virological response 12 weeks posttreatment(SVR12) via intention-to-treat (ITT) and modified intention-to-treat (mITT) analyses. Results: Of the 270 patients, 47.0%were infected with genotype 1b and 53.0% with genotype 2. ITT analysis revealed that SVR12 was achieved in 78.9% of all patients,77.2% in genotype 1b patients, and 80.4% in genotype 2 patients. Of the 21.1% of all patients who did not achieve SVR12, themajority of treatment failures were non-virologic failures (19.7%). mITT analysis revealed that SVR12 was achieved in 98.2% of allpatients, 98.0% in genotype 1b patients, and 98.3% in genotype 2 patients. Almost half of all patients experienced one or moreadverse events (43.3%), leading to 2.6% discontinuing scheduled treatment. The most common adverse event was anemia. Conclusions: Direct-acting antiviral-based treatment regimens showed high effectiveness and safety. Non-virological factors, suchas premature treatment discontinuation due to adverse events or loss of follow-up, were the major disruptors in achieving SVR12. KCI Citation Count: 0